Prognostic value of radial peripapillary capillary density for visual field outcomes in pituitary adenoma: A case-control study. (June 2022) - Tang, Yang; Jia, Wang; Xue, Zhan; Yuan, Linhao; Qu, Yuanzhen; Yang, Liu; Wang, Lina; Ma, Xiaochen; Wang, Meizi; Meng, Lei; Lei, Kun; Lu, Wen; et al.
Highlights: Pituitary adenoma causes optic chiasm compression leading to visual field defects. Visual prognoses following transsphenoidal surgery remain controversial. Radial peripapillary capillary density before surgery is a known prognostic factor. Monitoring vessel density may aid in determining the optimal timing for surgery. Abstract: Pituitary adenomas are known to cause optic chiasmal compression leading to visual field (VF) defects. Herein, we analysed the factors influencing early VF recovery following transsphenoidal surgery and explored the significance of retinal vessel density parameters in predicting prognoses. We collected data of 50 patients with pituitary adenoma and an abnormal VF prior to surgery. Patients were categorised into VF recovery (n = 25) and non-recovery (n = 25) groups within 1 week postoperatively. The VF, optic chiasm form, tumour volume, retinal thickness, and vessel density parameters were measured. The χ 2 test was used for single-factor analyses, and odds ratios (ORs) for each factor were calculated. Logistic regression was implemented to determine interactions between radial peripapillary capillary (RPC) density and other factors. Tumour volume (≥5 cm 3, OR = 5.09), duration of visual symptoms (≥6 months, OR = 6.00), preoperative VF (mean deviation [MD] < -10 dB, OR = 6.77), thin retinal nerve fibre layer (OR = 9.04), ganglion cell layer complex thickness (OR = 7.67), and RPC density (whole ≤ 48%; OR = 15.58; temporal ≤ 49.3%; OR = 14.64) were found to be risk factors for postoperative VF recovery. After adjusting for these factors, RPC density was a dependent factor affecting VF recovery in patients with pituitary adenoma. RPC density seemed to be a stronger indicator than preoperative MD, tumour volume, duration of visual symptoms, or retinal thickness for predicting early VF recovery following optic chiasm decompression, thus helping surgeons determine the optimal timing of surgery and formulate effective treatment plans.